Tall story - Gourlay, Candy (Yearling, 2012)
Andi, a short girl with big dreams, wishes many things, but most of all she wishes to be reunited with her long-lost brother, Bernardo. When her wish comes true, Andi is shocked to see that Bernardo is eight feet tall.